First dorsal metacarpal artery islanded flap: A useful flap for reconstruction of thumb pulp defects - Chetan Satish; Sunit Nema (Indian Journal of Plastic Surgery)
Thumb pulp defects are commonly due to avulsion injuries. It is very important to reconstruct these defects using sensate flaps as the thumb pulp needs to be sensate for implementing the various functions of the thumb. A very good option for coverage of these defects is the islanded first dorsal metacarpal artery flap. Our study was done over a period of 2 years and involved 9 consecutive cases of thumb pulp defects treated at our institution. The patients included 8 males and 1 female, ranging in age from 16 to 51 years old. The flap size ranged from 2 × 1.5 cm to 5 × 3 cm. We had only one complication in the form of partial flap necrosis, which fortunately healed following debridement without the need for a secondary procedure. All our cases were done under local anesthesia with tourniquet control. All the patients had good fine touch and average two-point discrimination of 6 mm, which was satisfactory. Our good results further reinforce the islanded first dorsal metacarpal artery flap as one the best flaps for sensate reconstruction of thumb pulp defects. It replaces the soft tissue loss at the thumb pulp with minimal donor site morbidity and with good return of thumb pulp sensation.